Factors Caused No Diet Compliance With Elderly With Diabetes Mellitus In The Region Working Health Health Door Of Sibolga City Year 2019 - Della Winda Gultom; Mei Yati Simatupang (Institute of Computer Science (IOCS), 2019)
Diabetes Mellitus (DM) or diabetes abbreviated is a health disorder in the form of a collection of symptoms caused by an increase in blood sugar (glucose) levels due to insulin deficiency or resistance. This study aims to determine the factors that cause dietary non-compliance in the elderly with diabetes mellitus in the work area of the Pintu Angin City Health Center in Sibolga City in 2018. The research design used was analytical descriptive. Sampling technique is accidental sampling as many as 86 respondents. The measuring instrument used is a questionnaire sheet. Analysis of the data using the Chi Sguare Test Statistical test.